Drought and society: Scientific progress, blind spots, and future prospects. (23rd January 2022) - Savelli, Elisa; Rusca, Maria; Cloke, Hannah; Di Baldassarre, Giuliano
Abstract: Human activities have increasingly intensified the severity, frequency, and negative impacts of droughts in several regions across the world. This trend has led to broader scientific conceptualizations of drought risk that account for human actions and their interplays with natural systems. This review focuses on physical and engineering sciences to examine the way and extent to which these disciplines account for social processes in relation to the production and distribution of drought risk. We conclude that this research has significantly progressed in terms of recognizing the role of humans in reshaping drought risk and its socioenvironmental impacts. We note an increasing engagement with and contribution to understanding vulnerability, resilience, and adaptation patterns. Moreover, by advancing (socio)hydrological models, developing numerical indexes, and enhancing data processing, physical and engineering scientists have determined the extent of human influences in the propagation of drought hazard. However, these studies do not fully capture the complexities of anthropogenic transformations. Very often, they portray society as homogeneous, and decision‐making processes as apolitical, thereby concealing the power relations underlying the production of drought and the uneven distribution of its impacts. The resistance in engaging explicitly with politics and social power—despite their major role in producing anthropogenic drought—can be attributed to the strong influence of positivist epistemologies in engineering and physical sciences. We suggest that an active engagement with critical social sciences can further theorizations of drought risk by shedding light on the structural and historical systems of power that engender every socioenvironmental transformation. This article is categorized under: Climate, History, Society, Culture > Disciplinary Perspectives Abstract : The figure exemplifies the four interrelated processes examined by engineering and physical sciences on drought risk and society over the past two decades. The intersection and direction of the arrows reflect respectively the interrelation and the evolution of these processes.